2007
DOI: 10.1159/000112823
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl Sulfate Reduces Superoxide Scavenging Activity in the Kidneys of Normal and Uremic Rats

Abstract: Background/Aim: Indoxyl sulfate (IS) is a uremic toxin that accelerates the progression of chronic renal failure (CRF). This study aimed at determining whether IS impairs antioxidative systems (redox status) in the kidney. Methods: IS was orally administered to normal and subtotally nephrectomized (three fourths and five sixths) rats (CRF rats) for 2 weeks. By use of in vivo and ex vivo electron spin resonance spectroscopy, the kidney redox status was evaluated using carbamoyl-PROXYL as a radical spin probe in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…Also, other groups reported that indoxyl sulfate promoted oxidative stress in endothelial cells and the kidney. [16][17][18][19] These results strongly suggest the involvement of uremic toxins in the development of atherosclerosis. AST-120 has been known to decrease serum levels of indoxyl sulfate significantly in CKD rat models and also in CKD patients.…”
Section: Discussionmentioning
confidence: 71%
“…Also, other groups reported that indoxyl sulfate promoted oxidative stress in endothelial cells and the kidney. [16][17][18][19] These results strongly suggest the involvement of uremic toxins in the development of atherosclerosis. AST-120 has been known to decrease serum levels of indoxyl sulfate significantly in CKD rat models and also in CKD patients.…”
Section: Discussionmentioning
confidence: 71%
“…All rats underwent five-sixths renal ablation using the method described earlier. 17,19 Eight weeks later, the subtotally nephrectomized rats (age 17 weeks) were divided randomly into two groups (n¼12 in each group): the first group was fed a normal diet (MF; Oriental Yeast, Osaka, Japan) (Nx) and the second group was fed a normal diet containing 0.4 g of AST-120 per 100 g body weight per day (Kureha, Tokyo, Japan) (Nx+AST). Age-matched sham-operated rats fed a normal diet (Sham) were used for comparison.…”
Section: Animal Preparationmentioning
confidence: 99%
“…17 In addition, IS induced free radical production in renal proximal tubular cells 18 and reduced superoxide scavenging activity in the kidneys of normal and uremic rats. 19 We previously showed that endothelial dysfunction was associated with enhanced vascular oxidative and nitrative stress in rats with obesity and renal injury. 20,21 The aim of this study was to determine whether AST-120 improves endothelial dysfunction and reduces vascular oxidative/nitrative stress in subtotally nephrectomized rats.…”
Section: Introductionmentioning
confidence: 97%
“…A 5/6-subtotal nephrectomy (STNx) rat model showed a significant 6.6-fold (65.7 μmol/L) increase in serum IS levels at 2 weeks after 5/6-STNx compared with sham animals, whereas a nonsignificant 3.7-fold (37.1 μmol/L) increase is observed in a 3/4-STNx model. 126 Importantly, an increase in circulating IS levels can occur in the early stages (2 and 3) of CKD, 127 and the combined prevalence of stages 2 and 3 is 67% of all CKD stages; 128 the harmful biological activity of elevated IS, therefore, should receive therapeutic attention before consideration of renal replacement therapy.…”
Section: Is Indoxyl Sulfate a Culprit Inmentioning
confidence: 99%
“…141 IS administration also impaired renal superoxide scavenging activity that is associated with renal dysfunction in uremic (3/4-and 5/6-STNx) rats. 126 There also is evidence that the profibrotic and oxidative stress-inducing effects of IS may be interrelated. One study demonstrated that an antioxidant can suppress IS-induced NF-κB activation in proximal tubular cells, and inhibition of NF-κB in turn suppressed TGF-β1 protein expression in uremic rats.…”
Section: Kidneymentioning
confidence: 99%